Chapter 2: What is decolonisation? - Mercier, Ocean Ripeka (Imagining Decolonisation, 2020)

Gender, Populism and Jacinda Ardern - Curtin, Jennifer; Greaves, Lara (A Populist Exception? : The 2017 New Zealand General Election / Edited By Jack Vowles and Jennifer Curtin., 2020)
Keywords: Elections & referenda; New Zealand; authoritarianism; elections; inclusivity; politics; populism; vote choice

Chapter 5: Where to next? Decolonisation and the stories in the land: Imagining Decolonisation - Jackson, Moana (Imagining Decolonisation, 2020)
Keywords: colonisation; decolonisation; hapū politics; iwi politics; rangatiritanga; tikanga | indigenous law

Māori resource management innovations - Bargh, Maria (Routledge Handbook of Critical Indigenous Studies, 2020)
The historical context of colonial legacies and capitalist policies are shaping responses to climate change but so too are non-capitalist and alternative-capitalist practices. Indigenous peoples’ world-views are commonly argued to align with non-capitalist approaches and often said to be the answer to climate change. However, Indigenous peoples are never only ‘ecological natives’ ‘living at one with nature’ but have multiple roles and identities in the political economy. Indigenous world-views could be used in ways to support capitalist practices and policies (which many argue have caused climate change) or to support alternative-capitalist practices (which others argue promote harmonious relationships between humans and the planet).
Keywords: capitalism; climate change; environment

Māori Interests and Rights: Four Sites at the Frontier - Bargh, Maria; Jones, Carwyn (Public Policy and Governance Frontiers in New Zealand, 2020)
Keywords: crown policy; government; iwi politics; kaitiakitanga; kāwanatanga; māori rights; rangatiratanga

Chapter 40: Indigenous finance: treaty settlement finance in Aotearoa New Zealand - Bargh, Maria (The handbook of diverse economies, 2020)
"Theorising and illustrating diverse, more-than-capitalist economies, this broad-ranging Handbook presents ways in which it is possible to imagine and enact other ways of being. It gathers together empirical examples of diverse economic practices and experiments from across the world, framed by in-depth discussions of key theoretical concepts. Organised into thematic sections, the Handbook moves from looking at diverse forms of enterprise, to labour, transactions, property, and finance as well as decentred subjectivity and diverse economies methodology. Chapters present a wide diversity of economic practices that make up contemporary economies, many of which are ignored or devalued by mainstream economic theory. Pushing the boundaries of economic thinking to include more than human labour and human/non-human interdependence, it highlights the challenges of enacting ethical economies in the face of dominant ways of thinking and being. Economic geography, political economy and development studies scholars will greatly appreciate the empirical examples of diverse economic practices blended with theory throughout the Handbook. It will also benefit policy-makers and practitioners working within diverse economies, or looking to create more ethical ways of living"– Provided by publisher.
Keywords: colonisation; economic aspects; governance; land loss; land ownership; tiriti o waitangi/treaty of waitangi; treaty settlements

Māori and the 2017 General election: party, participation, and populism - Greaves, Lara; Hayward, Janine (A Populist Exception? The 2017 New Zealand General Election, 2020)
Keywords: elections; kāwanatanga; māori electorates; māori seats; political participation; political parties; te pāti māori; voter turnout

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination